2003
DOI: 10.1016/s1567-1356(02)00186-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of enhanced xylose reductase activity on xylose consumption and product distribution in xylose-fermenting recombinant

Abstract: Recombinant Saccharomyces cerevisiae TMB3001, harboring the Pichia stipitis genes XYL1 and XYL2 (xylose reductase and xylitol dehydrogenase, respectively) and the endogenous XKS1(xylulokinase), can convert xylose to ethanol. About 30% of the consumed xylose, however, is excreted as xylitol. Enhanced ethanol yield has previously been achieved by disrupting the ZWF1 gene, encoding glucose-6-phosphate dehydrogenase, but at the expense of the xylose consumption. This is probably the result of reduced NADPH-mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 34 publications
(65 reference statements)
5
61
1
Order By: Relevance
“…This observation was found to correlate almost perfectly with higher xylose reductase / xylitol dehydrogenase activity ratios, as was previously reported for strains without xylulokinase overexpression (Walfridsson et al, 1997). Since increased xylose reductase activities have been reported to decrease the xylitol yield in the xylulokinase overexpressing TMB3001 strain (Jeppsson et al, 2003b), we cannot exclude, however, that other causes may also be responsible for xylitol accumulation. One such cause may be, for instance, increased intracellular NADPH levels, which have been shown to increase the tolerance to lignocellulose hydrolysate (Jeppsson et al, 2003a) observed also in the industrial strains analyzed here.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This observation was found to correlate almost perfectly with higher xylose reductase / xylitol dehydrogenase activity ratios, as was previously reported for strains without xylulokinase overexpression (Walfridsson et al, 1997). Since increased xylose reductase activities have been reported to decrease the xylitol yield in the xylulokinase overexpressing TMB3001 strain (Jeppsson et al, 2003b), we cannot exclude, however, that other causes may also be responsible for xylitol accumulation. One such cause may be, for instance, increased intracellular NADPH levels, which have been shown to increase the tolerance to lignocellulose hydrolysate (Jeppsson et al, 2003a) observed also in the industrial strains analyzed here.…”
Section: Discussionsupporting
confidence: 86%
“…The third-fast xylose-fermenter, BH42, was among the strains with the lowest xylose reductase activities (Table II). Thus, elevated reductase activity may be helpful to increase the xylose fermentation rate (Jeppsson et al, 2003b), but is clearly not essential for this trait.…”
Section: Fermentation Performance In Minimal Mediummentioning
confidence: 99%
“…Since this NADH-reoxidizing reaction is stoichiometrically coupled to the anabolic ammonium requirement, however, the possibilities for complete elimination of xylitol and glycerol accumulation appear to be limited. In the second case, xylose reductase expression levels were increased in a zwf1 mutant with an interrupted pentose phosphate pathway (17). The optimal expression level increased the ethanol yield by 10% and the fermentation rate by 120%.…”
Section: Discussionmentioning
confidence: 96%
“…To estimate the fluxes through the phosphoketolase pathway, the corresponding pathway was implemented in the model as a single reaction that converts xylulose-5-P and NADH to glyceraldehyde-3-P, acetaldehyde, and NAD ϩ . Since xylose reductase is also able to convert dihydroxyacetone phosphate to glycerol-3-P using both NADH and NADPH (17), the in vivo cofactor usage of xylose reductase is not assessable with a stoichiometric model. Thus, the cofactor usage ratio of the xylose reductase was assumed to remain unaltered, to maintain a determined system of linear equations (30).…”
Section: Methodsmentioning
confidence: 99%
“…Two types of xylose-assimilating pathways have been identified and used to engineer xylose-utilizing S. cerevisiae strains. One is the redox cofactor-dependent xylose reductase (XR)/xylitol dehydrogenase (XDH) pathway (8)(9)(10)(11)(12)(13)(14)(15), and the other is the redoxneutral xylose isomerase (XI) pathway (16)(17)(18)(19)(20)(21)(22)(23). Introduction of the XR/XDH pathway into S. cerevisiae by metabolic engineering approaches has been widely studied, but redox imbalance is a key problem, because XR can use both NADPH and NADH, while XDH uses NAD ϩ exclusively (6,24).…”
mentioning
confidence: 99%